THE ROLE OF ZIS FUND DISTRIBUTION (ZAKAT, INFAQ, ALMS) IN EMPHASIZING POVERTY LEVELS THAT AFFECT THE ECONOMY DURING THE COVID-19 PANDEMIC IN JAMBI PROVINCE - Paulina Lubis; Ary Dean Amri (Journal of Business Studies and Management Review, 2021)
This article aims to determine the distribution of ZIS Funds (Zakat, Infaq, Alms) in suppressing poverty levels that impact the economy during the Covid-19 pandemic outbreak in Jambi province. The method used is descriptive-quantitative and data collection through literature study and documentation in interviews with 70 respondents. Data were analyzed using the Likert scale method and multiple linear regression analysis. The result is that part of the perception/understanding of religion has a positive and significant effect on income levels, partially service variables have no and insignificant effect on income levels, partially, service variables have a positive and significant effect on income levels. So, it can be concluded that the perception/understanding of religion, service, and decisions have a simultaneous (combined) and significant effect on income levels.